Associations between age of menarche, early sexual debut and high‐risk sexual behaviour among urban Tanzanian schoolgirls: A cross‐sectional study. Issue 3 (15th February 2023) - Whitworth, Hilary S.; Baisley, Kathy J.; Nnko, Soori; Irani, Julia; Aguirre‐Beltran, Aura; Changalucha, John; Crucitti, Tania; Francis, Suzanna; Hashim, Ramadhan; Hansen, Christian Holm; Hayes, Richard J.; Buvé, Anne; et al.
Abstract: Objectives: This cross‐sectional survey aimed to explore associations between age of menarche, early sexual debut and high‐risk sexual behaviour among urban Tanzanian schoolgirls. Methods: Secondary schoolgirls aged 17–18 years from Mwanza, Tanzania, participated in structured face‐to‐face questionnaire‐based interviews, conducted by nurses and clinicians. Age of menarche was evaluated in categories of 11–12, 13–14, 15–16 or ≥17 years. Primary outcome measures were self‐reported early sexual debut (first vaginal sex at <16 years) and high‐risk sexual behaviour, including non‐use of condoms, having sex for gifts/money, having older sexual partners and/or other risky behaviours. Results: Of 401 girls enrolled, 174 (43.4%) reported prior vaginal sex. Prevalence of early sexual debut was 14.2% but pressured/forced sex and risky sexual behaviours were common. Adjusted for potential confounding, younger age at menarche was associated with early sexual debut (adjusted odds ratio for linear trend: 1.88 per category, 95% confidence interval: 1.21–2.92, p  = 0.005). This association remained after excluding girls with first sex at <8 years or experiencing pressure or force at first sex. Further, adjusted for potential confounding (including ever experiencing forced sex), early sexual debut was associated with high‐risk sexual behaviour (adjusted odds ratio: 2.85, 95% confidence interval: 1.38–5.88, p  = 0.004). Conclusions: Among urban Tanzanian school girls, younger age of menarche was associated with early sexual debut, and early sexual debut was associated with high‐risk sexual behaviour. Researchers and public health professionals developing and delivering interventions aimed at preventing adverse sexual health outcomes should consider the impact of these early biological and sexual exposures.